Exploration of Ethnomathematics in Umpet Batu Game - Hakim, Irsyad Malik; Soebagyo, Joko (Unnes Journal of Mathematics Education, 2025)
Ethnomathematics is an interesting learning resource because it connects the surrounding culture with mathematical concepts. This research focuses on exploring ethnomathematics in one of the games from DKI Jakarta, namely the game of umpet batu. The ethnographic approach is used to reveal the mathematical concepts in the game of umpet batu with data collection techniques through observation, interviews, and documentation, then further discussion related to mathematical concepts with mathematics teachers who know the game of umpet batu. The results showed that the game of umpet batu has simple mathematical concepts, namely basic arithmetic, probability, and flat geometry at the elementary and junior high school levels in different phases. The existence of learning resources with traditional games can help students understand math concepts in a real form and can preserve the traditional game itself.